Easy, Green and Safe Carbonylation Reactions through Zeolite‐Catalyzed Carbon Monoxide Production from Formic Acid. Issue 13 (11th September 2015) - Losch, Pit; Felten, Anne‐Sophie; Pale, Patrick
Abstract Zeolites with the right shape and acid site density and strength, such as certain ZSM‐5 forms, were able to cleanly decompose formic acid to carbon monoxide (CO), and the latter could be directly used in palladium‐catalyzed carbonylation reactions. A simple two‐reactor system was designed to produce CO conveniently and then further react this gas in a safe way. The two‐reactor system is particularly cheap, easy to set up and use. In addition, the carbonylation conditions without pressure allowed for very efficient CO incorporation, with only 1% of palladium(II) chloride (PdCl2) and Xantphos.